The immortals: faces of the incredible in Buddhist Burma - Rozenberg, Guillaume (Topics in contemporary Buddhism, 2015)
From belief to believing -- Being a disciple, fashioning a cult -- The possessed -- In quest of invulnerability -- Trial by fire